IMPLEMENTASI METODE WAFA DALAM PEMBELAJARAN BACA AL-QUR’AN DI MTs DARUSSALAM BOARDING SCHOOL SAMARINDA - Nursubhan, Nursubhan; Lismina, Lismina; Sholihah, Aam Amaliatus (STIT Ibnu Rusyd Tanah Grogot, 2024)
The Al-Qur'an is the holy book of Muslims which functions as a guide for all humans, so when reading the Al-Qur'an you must try to be able to read it well. In this case, it can be studied in learning to read the Al-Qur'an, in learning to read the Al-Qur'an there are also various methods. The aim of this research is to determine the implementation of the wafa method in learning to read the Al-Qur'an. The researcher chose MTs Darussalam Boarding School Samarinda as the research location because this madrasah uses the wafa method in learning the Al-Qur'an, because this method does not yet exist in other madrasas or schools in Samarinda. This type of research is descriptive qualitative research. With data collection techniques using observation, interviews and documentation. The primary sources for this research are the Head of Madrasah, Deputy Head of Curriculum, Qur'an Coordinator and Students. The secondary data source used is a general description of MTs Darussalam Boarding School Samarinda. Data analysis techniques use data collection, data reduction, data presentation, and drawing conclusions. The data validity technique uses triangulation. The research results show that the implementation of the wafa method in learning to read the Al-Qur'an at MTs Darussalam Boarding School Samarinda consists of three stages: planning, implementation and evaluation. The planning stage includes tasnif, level grouping, level exam, and tahfidz grouping. The implementation process uses the TTG guidebook or Wafa recitation book, by applying the 5P concept: opening, experience, teaching, assessment, and closing. The evaluation stage involves meetings, assessments, testing of students before the level exam by the Qur'an coordinator, and Wafa method exam questions. Supporting factors include madrasa support by providing Wafa books, creative young ustadz and ustadzah, as well as adequate room facilities. Inhibiting factors include limited student knowledge, lack of student seriousness, teacher busyness, lack of teacher reading fluency, lack of teacher certification, lack of teaching aids, inactivity in playing MP3s, poor implementation of SOPs, lack of tone mastery, and lack of vocals.